The Role of Obstetrician in Reducing the Risks of Childhood Allergy Related to Cesarean Birth: A Literature Review - Rima Irwinda; Febriansyah Darus; Peby Maulina (Indonesian Nutrition Association, 2020)
Women’s decision on birth mode should consider its risks and benefits, including long-term risks of caesarean among children. This study aims to present the current available evidences on the risks of caesarean towards childhood allergy and how an obstetrician could prevent this outcome through nutrition and education. We searched articles from several online databases about the link between caesarean, childhood allergy, and prenatal intervention. There were significant risks of childhood asthma and food allergy, but it was still unclear for allergic rhinitis and atopic dermatitis. Nutritional intervention could be done for pregnant women with consumption of probiotics and vitamin D supplementation. In addition, prenatal education is necessary to prepare better childhood outcomes.